Behaviour of steel-confined concrete - Zeng, Hong (2009)
A number of investigations have been carried out in the past into the strength and deformation characteristics of plain concrete subjected to multiaxial stress states, the confinement being provided hydrostatically. In practice, confinement in concrete is often provided by steel reinforcement in the form of spirals or ties, such as in columns. The expressions for the constitutive relationships of confined concrete resulting from the hydrostatic tests on plain concrete cannot be applied directly to laterally reinforced concrete, because there are major differences between confinement due to lateral steel reinforcement and confinement due to hydrostatic pressure. Firstly, while the hydrostatic lateral pressures applied to the plain concrete tests are uniformly distributed, confining pressures are applied by lateral reinforcement along discrete lines and vary along the ties as well as between them. Secondly, the hydrostatic pressure on the plain concrete is usually applied independent of the deformation of the specimen, while the confining stress given by the lateral reinforcement is a function of the lateral strain of the concrete under the axial load. Various analytical models for the behaviour of concrete confined by circular spirals and rectilinear ties have been proposed by past researchers. These models are empirical or semi-empirical, mainly based on results of tests on column specimens; some consisted of attempts to incorporate constitutive models of plain concrete under triaxial conditions into the analysis.